Implementing the Merdeka Curriculum in Chemistry Learning Through Tutoring: A Qualitative Study at Madrasah Aliyah Darul Funun El Abbassiyyah - Ratna Furi; Abdullah A. Afifi; Mona Eliza (IDRIS Darulfunun Institute, 2025)
The implementation of the Merdeka Curriculum emphasizes differentiated learning that accommodates students' diverse abilities, interests, and learning needs. In chemistry education, this approach is particularly important because students often experience difficulties in understanding abstract concepts that require strong conceptual reasoning. This study aims to examine the implementation of the Merdeka Curriculum in chemistry learning through a tutoring program at Madrasah Aliyah Darul Funun El Abbassiyyah. A descriptive qualitative research design was employed to provide an in-depth description of the implementation process. The study used the researcher as the primary research instrument, while data were collected through classroom observations and interviews. The collected data were analyzed descriptively by identifying and interpreting phenomena related to the implementation of tutoring in chemistry learning. The findings reveal that students possess diverse levels of academic ability, learning interests, and talents, requiring instructional approaches that extend beyond regular classroom teaching. The school implements an additional tutoring program outside regular instructional hours to provide more personalized guidance according to students' characteristics and academic potential. Through this program, teachers are able to identify students' competencies, monitor their conceptual understanding of chemistry, and facilitate the development of their interests and talents. The tutoring activities also support students' preparation for academic competitions, including the National Science Olympiad (OSN) and the Madrasah Science Competition (KSM), where students have achieved notable accomplishments. These findings indicate that tutoring serves as an effective strategy for implementing the principles of the Merdeka Curriculum by supporting differentiated instruction and optimizing students' academic development. The study concludes that integrating tutoring into chemistry learning provides meaningful opportunities for identifying and developing students' competencies, interests, and talents, while strengthening the implementation of the Merdeka Curriculum in the Madrasah context.